2015
DOI: 10.18632/oncotarget.4355
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin inhibits MEK1/2

Abstract: Cisplatin (cDDP) is known to bind to the CXXC motif of proteins containing a ferrodoxin-like fold but little is known about its ability to interact with other Cu-binding proteins. MEK1/2 has recently been identified as a Cu-dependent enzyme that does not contain a CXXC motif. We found that cDDP bound to and inhibited the activity of recombinant MEK1 with an IC50 of 0.28 μM and MEK1/2 in whole cells with an IC50 of 37.4 μM. The inhibition of MEK1/2 was relieved by both Cu+1 and Cu+2 in a concentration-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The number of differentially expressed genes annotated with these twelve terms was far too large for further analysis. Therefore, we focused on those terms, for which a contribution to the mode of action of cisplatin or possible involvement in chemoresistance has been described in the literature, namely NOTCH receptor signalling [ 24 , 25 ], the VEGFR signalling pathway [ 26 , 27 ], the cell surface receptor signalling pathway [ 28 , 29 ] and the Ras protein signal transduction pathway [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of differentially expressed genes annotated with these twelve terms was far too large for further analysis. Therefore, we focused on those terms, for which a contribution to the mode of action of cisplatin or possible involvement in chemoresistance has been described in the literature, namely NOTCH receptor signalling [ 24 , 25 ], the VEGFR signalling pathway [ 26 , 27 ], the cell surface receptor signalling pathway [ 28 , 29 ] and the Ras protein signal transduction pathway [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…DOK1 is known as a negative regulator of Ras [ 36 , 39 ]. HRas belongs to the Ras oncogene family being central to the MAPK/ERK pathway [ 30 ]. However, the analysis of ERK activation revealed no significant differences between sensitive and resistant cell line ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…The specific structure of cisplatin may disrupt the MEK1-cRaf complex resulting in MAST1 as the sole kinase remaining in the complex. Previous reports showed that cRaf binding sites in MEK1 consist of Ser221/217, whereas predicted cisplatin binding sites in MEK1 are Met56 and Cys104 (Caunt et al, 2015; Yamamoto et al, 2015). We revealed that cisplatin directly binds to MEK1 but not cRaf.…”
Section: Discussionmentioning
confidence: 96%
“…Over a time course of cisplatin treatment in resistant and sensitive cell lines, the authors show that cRAF is displaced from MEK1 within as little as 1 hr of cisplatin exposure. Cysteine 142 was previously predicted as one of the copper-binding sites in MEK1 (Yamamoto et al, 2015), so it is tempting to speculate that cisplatin may displace copper from MEK1. It would also be intriguing to determine whether cisplatin resistance markers, notably the copper efflux transporters (ATP7A, ATP7B), are upregulated during cisplatin treatment to decrease competition by copper for binding to MEK1 (Turski et al, 2012).…”
Section: Previewsmentioning
confidence: 99%